2008
DOI: 10.1080/10641950802000943
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension During Pregnancy in Portugal

Abstract: In Portugal, the prevalence of hypertensive disorders diagnosed during pregnancy seems to be lower than that reported in most countries, but these disorders have a significant effect on pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 6 publications
2
16
4
Order By: Relevance
“…In our study, the prevalence of hypertensive disorders during pregnancy was lower than reported in other industrialized nations (Bodnar et al, 2007;Gaillard et al, 2011;Roberts et al, 2005), and also slightly lower than the 5.6% previously described in a national survey for the Portuguese population (Povoa et al, 2008). Since the authors reported no significant differences in prevalence across the country (Povoa et al, 2008) we expected to find a similar prevalence. Despite the high proportion of participation in our cohort, it is possible that the refusals occurred mainly in cases with higher maternal and/or perinatal According to the Institute of Medicine recommendations (Rasmussen & Yaktine, 2009).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In our study, the prevalence of hypertensive disorders during pregnancy was lower than reported in other industrialized nations (Bodnar et al, 2007;Gaillard et al, 2011;Roberts et al, 2005), and also slightly lower than the 5.6% previously described in a national survey for the Portuguese population (Povoa et al, 2008). Since the authors reported no significant differences in prevalence across the country (Povoa et al, 2008) we expected to find a similar prevalence. Despite the high proportion of participation in our cohort, it is possible that the refusals occurred mainly in cases with higher maternal and/or perinatal According to the Institute of Medicine recommendations (Rasmussen & Yaktine, 2009).…”
Section: Discussioncontrasting
confidence: 54%
“…Although this rate was lower than in other countries (Bodnar et al, 2007;Gaillard et al, 2011;Roberts et al, 2005), pre-term birth, small for gestational age newborns and foetal death were more frequent in women with hypertensive pregnancies (Povoa et al, 2008).…”
Section: Introductioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The prevalence of the different hypertensive disorders in our study is largely in agreement with other reports. [21][22][23][24][25][26] Pre-eclampsia has been reported to complicate between 1.4% and 7% of all pregnancies, 13,21,22,24,27 and gestational hypertension between 1% and 4.3% of all pregnancies. 21,22,24,25 The prevalence of chronic hypertension varies between 0.2% and 5%, and the highest prevalence is among the oldest women.…”
Section: Discussionmentioning
confidence: 99%
“…Antihypertensive drugs are routinely prescribed in pregnancy to reduce the progression to severe hypertension (systolic blood pressure of ≥160 mmHg). 1 Between 0.6% and 2% of women have chronic hypertension during pregnancy, [2][3][4][5][6] and an additional 6-7% develop hypertension during gestation. 7 Severe hypertension during pregnancy can lead to substantial morbidity for the mother and the fetus.…”
Section: Introductionmentioning
confidence: 99%